Changing Tendencies of Patients with Electrical Burns in Lithuania from 2016 to 2020 - Sipavičius, Viljamas; Rimdeika, Rytis (Lietuvos chirurgija, 2023)
Background. Electrical injuries are not common, however these injuries are severe. The burns cause damage for both superficial and deep layers of skin, as well as deeper tissues, and can lead to necrosis. Morbidity and mortality from electrical injuries are quite high and have physical and psychological consequences. Epidemiological analysis of electrical burns helps to understand patterns of these devastating injuries and to plan further treatment strategies. The objective of the study is to evaluate the number of patients affected by electrical injuries in Lithuania from 2016 to 2020. Methods. Data for the study were used from the Health Information Center of the Institute of Hygiene, calculated from the information system SVEIDRA of the State Health Insurance Fund under the Ministry of Health of Lithuania. Statistical analysis of the data was performed using IBM SPSS statistics 23.0 software. Using the Mann-Whitney criterion, a comparison was made between the percentage distributions of electrical injuries during the study period. Results. During five years (2016–2020), 355 people in total, 85 of them children, were affected by electrical injuries. Men were more likely to suffer from electric injuries. 80.4 percent males were affected and 19.6 percent females. Overall, electrical injuries decreased by 8.45 percent. The number of electrical injuries decreased by 3.66% in the children group and 4.79% in the adult group. Conclusions. After reviewing the research data, it can be concluded that from 2016 to 2020, there was decreased tendency of electrical injuries in Lithuania by 15.3% among children and by 6.29% among adults. Men were more likely to experience electrical injuries. Ongoing prevention strategies and measures in society and raising social awareness are key factors in reducing electrical injuries.
Keywords: electrical injuries; burns; changing trends